Insomnia Among Covid-19 Patients During Isolation Treatment in Inpatient Room of Indonesian Health Care Facilities - Tamara Nur Budiarti; Arina Dery Puspitasari; Alfian Nur Rosyid; Diah Indriani; Soenarnatalina Melaniani; Fatimatuz Zahra Oviary Satryo; Lily Aina; Nanda Ardianto; Melinda Putri Amelia Rachman; Fauzul Meiliani (Faculty of Public Health, Hasanuddin University, Makassar, 2022)
Insomnia was a problem of Covid-19 patients often moaned because the physical and psychological condition of patients are weak. This study aims to analyze the association between respondent’s characteristics, social factors, and medication adherence with insomnia when Covid-19 survivor become isolated patients. This study used a descriptive and analytical cross-sectional design. The study was conducted in August 2021. The population of this study was all Covid-19 survivors. The sample of this study was part of Covid-19 survivors with a total number of 191. Data were collected by an online questionnaire via google form and analyzed by chi-square test. Almost all respondents (83.77%) were female, and most of the respondents (73.30%) worked as health workers. The age mean of the respondents was 31.51 (SD 8.82, min=18, max=60). Insomnia was experienced by almost half of the respondents (41.36%). There was no association between sex (OR = 1.92, 95% CI 0.89-4.17; p=0.113), type of work (OR = 1.11, 95% CI 0.58-2.11; p=0.868), medication adherence (OR = 0.47, 95% CI 0.05-4.56; p=0.644), and motivation (p=0.269) with insomnia. There was an association between optimism (p=0.043) and discrimination (OR=4.19, 95% CI 1.86-9.43, p=0.001) with insomnia. Insomnia was experienced by almost half of isolated patients in inpatient rooms of Indonesian health care facilities. Factors associated with insomnia were optimism and discrimination. Treatment for Covid-19 patients should pay attention to their physical care and give psychological care.